Electromagnetic absorption properties of natural microcrystalline graphite. (15th January 2016) - Xie, Wei; Zhu, Xukun; Yi, Shihe; Kuang, Jiacai; Cheng, Haifeng; Tang, Wei; Deng, Yingjun
Abstract: An effective composite of natural microcrystalline graphite/low density polyethylene (MG/LDPE) was prepared by extrusion calendering method and the electromagnetic absorption properties of the composites were investigated. The morphology and structure of the MG were characterized by scanning electron microscopy, energy-dispersive X-ray microanalysis system, Raman spectroscopy and X-ray diffraction. It is interesting to find that two absorbing peaks appear at low frequency and high frequency with the thickness of 2.0–2.1 mm. Results show that the content and the particle size of MG have great effects on the electromagnetic absorption property of the MG/LDPE composites. Under the condition that the speed of ball-milling is 800 r/min, the bandwidth of MG/LDPE composites less than − 5 dB reaches 6.79 GHz, its less than − 10 dB comes to 3.02 GHz, and the reflectivity values are − 12.44 dB and − 20.46 dB. The remarkable electromagnetic absorption properties of MG/LDPE composite can attribute to the multiple absorbing mechanisms. It is believed that such a composite could serve as an attractive candidate for electromagnetic absorbers. Graphical abstract: Highlights: An effective composite of natural microcrystalline graphite/low density polyethylene was prepared by extrusion calendering method. It is interesting to find that two absorbing peaks appear at low frequency and high frequency with the thickness of 2.0–2.1 mm. The remarkable electromagnetic absorption properties of composite can be attributed to the multiple absorbing mechanisms. It is believed that such a composite could serve as an attractive candidate for electromagnetic absorbers.